PEMBELAJARAN BERBASIS MASALAH PADA MATERI KUBUS DAN BALOK DI KELAS VIII - Fauzi, Alex Haris (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2016)
This research was pre-experimental research begun with development research that aims to produce good learning instrument of problem based learning for cube and cuboid in 8th grade, describe the effectiveness of problem besed learning for cube and cuboid in 8th grade, and compare the learning outcomes of student taught by problem based learning with the learning outcomes of student taught by commonly conventional learning implemented in the school for cube and cuboid at 8th grade. The development of learning instrument used Plomp model. The learning instrument which had been gained were Lesson Plan, Students Worksheet, and Test Instruments.The data source of this study was the students at SMPN 3 Srono Satu Atap in academic year 2014/2015 with VIII-2 was trial class, VIII- 3 as implementative class, and VIII-1 as control class. Based on the trial results, that is the learning instrument that fulfill criteria of (1) valid, (2) practical (3) effective. Based on the results of descriptive analysis on experimental study concluded that problem based learning is effective for teaching cube and cuboid. This can be seen from 1)the teacher abilities are good, 2) the students activities are effective, 3) the students responses are positive, and 4) the learning outcomes of student is completed, there is 84,4 % of students who got ?70 for their score. Based on inferential statistical analysis, it be conclude that the learning outcomes of student taught by problem based learning with the learning outcomes of student taught by commonly conventional learning implemented in the school for cube and cuboid at 8th grade.